Assistance In Local Feed-Based Fermented Feed Processing As An Effort To Improve Pig Performance In Turaloa Village, Wolomeze Sub-District, Ngada District - Nicolaus Noywuli; Rembo, Egidius; Umbu Awang Hamakonda; Ferdinandus Bai; Maria Stefania Goo Kowe; Stefanus Venicreator Teda; Johanes Sago; Reinaldus Sue (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Success in livestock farming is highly dependent on 3 factors, namely seeds, feed and health. Feed factor is the factor that has the highest percentage reaching 60-70% in determining the success of livestock farming. Along with the high price of pig feed ingredients, the use of local feed ingredients is the right solution to meet the needs of pigs, but the obstacle faced is that the nutritional content of local feed ingredients is very low so that an appropriate innovation is needed to process local feed ingredients. The innovation that was built was fermentation technology. The purpose of this community service activity is to find out the technology of local feed ingredient fermentation using microbes found in livestock EM4. The method used is the training method and mentoring for processing pig feed based on local feed ingredients for the Nusa Aur group, Nggurununca Hamlet, Turaloa Village, Wolomeze District, Ngada Regency. The result of this community service activity is that the community included in the Nusa Aur group gains knowledge and skills to process pig feed based on local feed ingredients so that it can increase the productivity of the pigs being raised. The conclusion of this activity is that the provision of continuous and quality pig feed can be overcome, so that the growth and production levels of pigs will be optimal.